Responding to food supply shocks through global partnerships in technology development and transfer: the case of the IITAled biological control of cassava mealybug in subSaharan Africa - Alene, A.; Manyong, Victor M.; Coulibaly, O. (2006)
Partnerships involving national agricultural research systems (NARS), the Consultative Group on International Agricultural Research (CGIAR), universities, advanced research institutes, the private sector, civil society, non-governmental organizations, farmer organizations and international investors represent a global capacity to provide solutions to strategic problems and to fulfil the overall objective of combating rural poverty and food insecurity. Drawing on the experiences and achievements of the IITA-led biological control of the cassava mealybug in Sub-Saharan Africa, this paper gives an account of the role of global partnerships in technology development and transfer in addressing food security challenges. It concludes with implications for national and international agricultural research centers for an efficient, demand-driven technology development and delivery.